A typology of “infrastructure of the middle” in university food procurement in England and Canada: elaborating the “to” in “farm to cafeteria” - Stahlbrand, Lori (Raízes: Revista de Ciências Sociais e Econômicas, 2016)
This article introduces a new term – “infrastructure of the middle” – and explains how it helps understand how sustainability transition will happen in the food system. The evidence comes from 67 interviews with leaders of university food procurement initiatives in England and Canada. As founder and former president of the civil society organization which played a central role in the Canadian example, I bring a perspective informed by praxis, both as a practitioner and as a scholar applying Sustainability Transition Theory. I adapted the term infrastructure of the middle from Kirschenmann et al.’s concept of “agriculture of the middle”, which describes the midsize farms and ranches most at risk in a globalized food system. Infrastructure of the middle refers to the resources and networks that create a critical mass, enabling mid-size sustainable food producers to meet the needs of foodservice clients, especially public sector institutions.